2019
DOI: 10.3389/fpsyg.2019.00755
|View full text |Cite
|
Sign up to set email alerts
|

Overlooked Leadership Potential: The Preference for Leadership Potential in Job Candidates Who Are Men vs. Women

Abstract: Two experiments tested the value people attach to the leadership potential and leadership performance of female and male candidates for leadership positions in an organizational hiring simulation. In both experiments, participants ( Total N = 297) valued leadership potential more highly than leadership performance, but only for male candidates. By contrast, female candidates were preferred when they demonstrated leadership performance over leadership potential. The findings reveal an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 61 publications
2
34
0
Order By: Relevance
“…Women entrepreneurs may further experience a sense of low status in business networking. Indeed, evidence suggests that women are often judged on prior performance, while men are more often judged on potential competence (Player et al 2019). One recent study from the USA also showed that while men CEOs tended to be fired in the context of poor business performance, women CEOs tend to be replaced independent of firm performance (Gupta et al 2018).…”
Section: Examples Of Programme Supports To Address Symbolic Capitalmentioning
confidence: 99%
“…Women entrepreneurs may further experience a sense of low status in business networking. Indeed, evidence suggests that women are often judged on prior performance, while men are more often judged on potential competence (Player et al 2019). One recent study from the USA also showed that while men CEOs tended to be fired in the context of poor business performance, women CEOs tend to be replaced independent of firm performance (Gupta et al 2018).…”
Section: Examples Of Programme Supports To Address Symbolic Capitalmentioning
confidence: 99%
“…Previous research on individuals' preference for the potential for competence improvement [7,8,21] mostly adopted the paradigm of Experiment 3 in Tormala, Jia, & Norton's study [6]. In that paradigm, participants were asked to evaluate an individual with high achievement and high potential for decline and an individual with moderate achievement and high potential for improvement.…”
Section: Symmetric Biases Regarding Potential For Competence Improvemmentioning
confidence: 99%
“…Indeed, previous research showed a preference for individuals with high potential for improvement compared with individuals with high achievements [ 6 , 7 ]. However, the preference for the potential for improvement was verified mostly in the field of competence, such as leadership [ 6 8 ], creativity [ 9 ], and academic ability [ 6 ]. Thus, it is unclear whether individuals prefer the potential for moral improvement over a high level of morality.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we investigate the relationship between stereotype endorsement and stereotype reinforcement on how men (vs. women) and younger (vs. older) workers judge their own leadership potential. We focus on gender and age as both have been found to impact assessments of others' leadership potential (Hirschfeld and Thomas, 2011; Tresh et al, 2018; Player et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…A more plausible explanation is psychological biases against these groups in the form of subjective and unfavorable evaluations. Recent research has shown that gender is a boundary condition to the preference for potential (over past performance) in candidates for leadership positions (Player et al, in press). Specifically, we found that men are selected for leadership positions based on their future potential, whereas women are selected based on past performance (Player et al, in press).…”
Section: Introductionmentioning
confidence: 99%